Higher clozapine concentration-to-dose ratios at week 1 after initiation are associated with increased risk of clozapine-associated fever in Japanese patients with schizophrenia - Kikuchi, Yuki; Tanifuji, Hiroaki; Sakata, Mutsumi; Ikawa, Kazuro; Kume, Daisuke; Horikawa, Naoki; Ueno, Sota; Onuma, Yoshifumi; Ishihara, Masato; Onodera, Bunichiro; Toraiwa, Takeshi; Komatsu, Hiroshi; et al. (Frontiers in Psychiatry, 2025)
IntroductionThe clinical use of clozapine in the treatment of schizophrenia is sometimes halted due to its inflammatory side effects. However, no method has been established for preemptively identifying patients who are at high risk for these events. Therefore, in this study, we assessed whether the blood clozapine concentration-to-dose ratio (C/D) on day 8 after initiation could predict the risk of clozapine-associated fever.MethodPatients whose blood levels of clozapine were measured on day 8 after initiation were retrospectively investigated. The C/D ratio on day 8 was compared between patients who had fever after day 8 and those who did not.ResultsA total of 43 patients were included in the study. The range of C/D ratios on day 8 was from 0.35–4.0, with a median of 1.65. Patients with fever had significantly higher C/D ratios on day 8 than those without fever (2.33 vs. 1.47; P < 0.005).ConclusionMeasuring blood clozapine levels on day 8 may help to better estimate the risk of clozapine-associated fever in patients with schizophrenia.